TAMI-57. INDUCTION OF FERROPTOSIS PROMOTES IMMUNOGENIC CELL DEATH AND ACTIVATION OF THE IMMUNE MICROENVIRONMENT IN GLIOMA. (12th November 2021) - Argenziano, Michael; Banu, Matei; Dovas, Athanassios; Zhao, Wenting; Furnari, Julia; Higgins, Dominique; Upadhyayula, Pavan; Mahajan, Aayushi; Humala, Nelson; Sims, Peter; Bruce, Jeffrey N; Canoll, Peter
Abstract: Gliomas are immune cold tumors. Effective therapeutic strategies capable of inducing an immune response are lacking.Here we present evidence that ferroptosis, a form of iron-mediated lipid peroxidation-based cell death, may promote anti-tumor immunity via stimulation of phagocytosis and pro-inflammatory activities in microglia. While ferroptosis has shown promise in induction of glioma cell death, the immunogenic and microenvironmental effects of glioma ferroptosis are poorly understood. First, we tested the in vitro effects of the glutathione peroxidase 4 (GPX4) inhibitor RSL3, a ferroptosis inducer, on murine glioma cell lines. Using flow cytometry, we discovered that RSL3 treatment led to membrane translocation of the pro-phagocytic antigen calreticulin, known hallmark of immunogenic cell death, by an average log2-fold-change of 2.53 (p= 0.03) compared to DMSO-treated controls. This effect correlated with lipid peroxidation, as assessed by BODIPY-C11 staining. To further test the effects of ferroptosis on glioma cell-microglia crosstalk, we prepared acute brain tumor slices from both mouse and human glioma samples, and treated them with RSL3. Quantification of immunofluorescent staining from three independent human slice cultures after RSL3 treatment demonstrated a significant increase in calreticulin abundance as compared to control (p < 0.001). Importantly, this effect was significantly diminished with addition of ferrostatin, an inhibitor of ferroptosis, demonstrating that ferroptosis induction was directly responsible for calreticulin translocation. Single-cell RNAseq on mouse and human acute glioma slice cultures treated with RSL3 demonstrated significant overexpression of calreticulin in the tumor population, and positive enrichment of interferon signaling, antigen presentation, and phagocytosis ontologies in both tumor and myeloid compartments. These findings suggest that ferroptosis-induced translocation of calreticulin on the surface of glioma cells promotes activation of the local immune microenvironment by increasing tumor antigen presentation and pro-inflammatory cytokine release by tumor-associated microglia. Thus, ferroptosis-inducing drugs may promote anti-tumor immunity through the activation of immunogenic cell death signals.